The Modern Trends of Continuous Technological Education in Ukraine from the Perspective of European Integration - ZHERNOKLIEIEV, Igor (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
The paper examines, on the basis of modern domestic and foreign scientific sources, the state and trends in the sphere of life long education in Ukraine, followed by the prospect of joining the European educational space.